CP-346086 - Charles E. Chandler (Journal of Lipid Research, 2003)
A microsomal triglyceride transfer protein (MTP) inhibitor, CP-346086, was identified that inhibited both human and rodent MTP activity [concentration giving half-maximal inhibition (IC50) 2.0 nM]. In Hep-G2 cells, CP-346086 inhibited apolipoprotein B (apoB) and triglyceride secretion (IC50 2.6 nM) without affecting apoA-I secretion or lipid synthesis. When administered orally to rats or mice, CP-346086 lowered plasma triglycerides [dose giving 30% triglyceride lowering (ED30) 1.3 mg/kg] 2 h after a single dose. Coadministration with Tyloxapol demonstrated that triglyceride lowering was due to inhibition of hepatic and intestinal triglyceride secretion. A 2 week treatment with CP-346086 lowered total, VLDL, and LDL cholesterol and triglycerides dose dependently with 23%, 33%, 75%, and 62% reductions at 10 mg/kg/day. In these animals, MTP inhibition resulted in increased liver and intestinal triglycerides when CP-346086 was administered with food. When dosed away from meals, however, only hepatic triglycerides were increased. When administered as a single oral dose to healthy human volunteers, CP-346086 reduced plasma triglycerides and VLDL cholesterol dose dependently with ED50s of 10 mg and 3 mg, and maximal inhibition (100 mg) of 66% and 87% when measured 4 h after treatment. After a 2 week treatment (30 mg/day), CP-346086 reduced total and LDL cholesterol and triglycerides by 47%, 72%, and 75%, relative to either individual baselines or placebo, with little change in HDL cholesterol.Together, these data support further evaluation of CP-346086 in hyperlipidemia.